(untitled) (Journal of Accounting and Financial Studies ( JAFS ), 2024)
Purpose: Auditor’s professional judgment is among the main determinants of audit quality, which can be influenced by various factors. This study investigated the effect of auditors’ ethical ideology on their professional judgment and professional commitment and also the impact of auditors’ professional commitment on their professional judgment. Design/Methodology/Approach: The research variables were analyzed using the data collected by distributing 360 questionnaires among auditors in 2022, out of which 270 eligible completed questionnaires were retrieved. The collected data were analyzed using the structural equation modeling (SEM) 1. Methodology in the LISREL software. Findings: This data analysis showed that auditors’ ethical ideology had no direct significant effect on their professional judgment, but it significantly affects professional judgment indirectly through professional commitment. Originality/value: According to the authors, this study, according to the approach of moral ideology presented in the present article, no similar research has been found in Iran. This study provides empirical support from a theoretical perspective on the impact of professional commitment on the auditor’s ethical ideology. The results may be of interest to auditors and managers seeking the quality of financial reporting. Paper type: Research paper